Contact Allergy to Neem Oil. Issue 6 (November 2017) - de Groot, Anton; Jagtman, Berend A.; Woutersen, Marjolijn
Abstract : A case of allergic contact dermatitis from neem oil is presented. Neem oil (synonyms: Melia azadirachta seed oil [INCI name], nim oil, margosa oil) is a vegetable (fixed) oil obtained from the seed of the neem tree Azadirachta indica by cold pressing. Contact allergy to neem oil has been described previously in only 3 patients. The allergen(s) is/are unknown.